Estimasi kesesuaian perairan untuk marikultur berbasis kualitas air dan pendekatan spasial-temporal di Pulau Karampuang, Sulawesi Barat - Mahfud, Chairul Rusyd; Noor, Rahmat Januar; Nur, Fauzia; Ihsan, Muhammad Nur; Nur, Rahmi; Darsiani, Darsiani; Lestari, Dian; Surianti, Surianti (Agrokompleks, 2025)
Mariculture activities play a significant role in contributing to the country's foreign exchange, as many of its products are exported abroad. Mamuju Regency, situated in West Sulawesi Province, is part of the eastern region of Indonesia and boasts vast potential for mariculture due to its abundant natural resources. However, farmers face several challenges, particularly oceanographic factors such as large waves, variations in freshwater input, and nutrient concentrations from land-based activities. These factors can negatively impact aquaculture media and alter oceanographic conditions, potentially threatening cultivation. The goal of this study was to examine the spatial and temporal dynamics of oceanographic conditions and assess the feasibility of waters for mariculture activities. The research was conducted in the waters around Karampuang Island in Mamuju Regency, using a descriptive quantitative approach. This involved determining sampling stations, measuring water quality both in situ and ex situ, analyzing data to assess the suitability of the waters for mariculture, and creating a GIS-based land suitability map. The results show that the water conditions in Karampuang Island are pretty dynamic, with varying water quality parameters observed, indicating diverse suitability for mariculture. For seaweed cultivation, station 3 was categorized as quite suitable, while stations 1 and 2 were considered appropriate. However, for KJA system cultivation, only station 1 consistently supports cultivation. Further studies are needed to monitor the water quality periodically and conduct cultivation trials to optimize farming activities.